Polimorfismo da beta-lactoglobulina não afeta as caracterí sticas físico-químicas e a estabilidade do leite bovino - Botaro, Bruno Garcia; De Lima, Ygor Vinícius Real; Aquino, Adriana Augusto; Fernandes, Raquel Helena Rocha; Garcia, José Fernando [UNESP]; Dos Santos, Marcos Veiga (FapUNIFESP (SciELO), 2007)
The objective of this study was to evaluate the effect of beta-lactoglobulin polymorphism, breed and seasonality on physico-chemical characteristics and stability of bovine milk. Six Holstein-Zebu (H-Z) and five Holstein dairy herds were selected, of which 660 Holstein and 293 crossbred Holstein-Zebu milk and blood samples were collected, adding up 953 samples, distributed in two collecting periods at rainy and two at dry seasons. Each milk sample was analyzed for titratable acidity, pH, freezing point and milk ethanol stability, at the following ethanol concentrations: 70, 76, 80 and 84GL. Individual blood samples were submitted to polymerase chain reaction (PCR) for the determination of beta-lactoglobulin polymorphism. No effect of beta-lactoglobulin polymorphism was observed in physico-chemical characteristics of milk, in both studied breed. Breed effect for Holstein and H-Z, respectively, was observed on titratable acidity (16.16 and 17.07°D, while effect of seasonality (for rainy and dry seasons, respectively) was also observed on freezing point (-0.5411 and -0.5376°H). Effects of breed and seasonality on milk stability were observed (Holstein-Zebu milk was less stable on dry season), however, no effect of beta-lactoglobulin on milk stability was observed.

O objetivo deste trabalho foi avaliar o efeito do polimorfismo genético da beta-lactoglobulina, da raça e da sazonalidade sobre as características físico-químicas e estabilidade do leite bovino. Foram selecionados 5 rebanhos da raça Holandesa e 6 da Girolando. Amostras de leite e sangue foram coletadas de 660 vacas Holandesas e 293 Girolandos, num total de 953 amostras, obtidas em duas coletas na estação seca e duas na estação chuvosa. As amostras de leite foram submetidas à análise de acidez titulável, pH, crioscopia, e ao teste de estabilidade ao etanol (70, 76, 80 e 84ºGL). As amostras de sangue foram submetidas à reação em cadeia de polimerase, para determinação do polimorfismo da beta-lactoglobulina em ambas as raças estudadas. Não houve efeito do polimorfismo da beta-lactoglobulina sobre as características físico-químicas do leite. Observou-se efeito de raça (Holandesa e Girolando, respectivamente) sobre a acidez titulável (16,16 e 17,07°D), e da sazonalidade (estações chuvosa e seca, respectivamente) sobre a crioscopia (-0,5411 e -0,5376°H). Nas condições do estudo, observou-se efeito de raça e sazonalidade sobre a estabilidade do leite, com maior instabilidade do leite de Girolando, durante a estação seca. Não houve efeito do polimorfismo da beta-lactoglobulina sobre essa característica.
Beta-lactoglobulin polymorphism does not affect physico-chemical characteristics and milk stability
Keywords: Dairy cow; Ethanol stability test; Genetic variants; Milk physico-chemical properties; Bos; Bos indicus; Bovinae